"Still Blundering into Sense". Maria Edgeworth, her context, her legacy - Fantaccini, Fiorenzo; LEPRONI, Raffaella (Biblioteca di Studi di Filologia Moderna, 2019)
"Still Blundering into Sense". Maria Edgeworth, her context, her legacy. This collection of international contributions, as well as celebrating Maria Edgeworth's 250th anniversary, proposes some further investigation on two fundamental aspects of her thought and legacy, still little examined in depth: her interest in the education of the young (and of the adults supposed to educate them) in an empirical perspective, explicitly scientific, open to different religious confessions and addressed to all social classes; and the urge for a wider and shared tolerance for alterity. The various essays in the collection offer some insight on the multi-layered relationships between the universe of education and its relationship with the development of knowledge, literature - particularly children's literature - and pedagogy, as well as between women's emancipation and the development of both individual and social identity. Their common ground is a dialogic perspective aiming to connect areas of scholarship, which the academia generally classifies into separate research fields.